Real Estate Owners’ Early Thoughts on Lean IPD Implementation in Spain - José Javier Gil Sebastián; Manuel José Soler Severino (Buildings)
The construction industry faces persistent inefficiencies, with projects often failing to meet time, cost, quality, and other conditions of satisfaction. This study investigated real estate owners’ early perceptions of Lean Integrated Project Delivery (Lean IPD) as a potential solution, analyzing the acceptance of principles such as early stakeholder involvement, risk–reward compensation, and open-book accounting, among other key features in Lean IPD. A survey of 62 professionals in real estate development companies in Spain was conducted, analyzing their experience with collaborative contracts and Lean techniques, including Last Planner System and Target Value Design. Statistical methods such as hierarchical clustering and PLS-SEM modeling revealed two distinct groups: those receptive to Lean IPD’s economic mechanisms and those less inclined. While governance principles like early collaboration and team co-responsibility received widespread support, skepticism was noted toward economic transparency practices due to cultural and structural barriers. Additionally, the findings indicate a significant gap in formal training for Lean IPD. Despite challenges, there is strong interest in adopting Lean IPD, driven by its potential to address critical project inefficiencies. This study concludes that successful Lean IPD implementation requires strategic leadership from owners, targeted training programs, and a cultural shift within the industry to embrace collaborative and transparent practices.